Relações entre deglutição e qualidade vocal: análise ultrassonográfica e perceptiva - Freitas, Andréa Baldi de (2017)
Introduction: several methods of imaging have been used to investigate the swallowing process. Ultrasound images (USG) have stood out among the different techniques to assess the swallowing function, since it does not expose subjects to radiation, is low-cost, and enables the offering of food in usual situations. To our knowledge, to the present time there are no studies that establish a relation between swallowing and vocal quality using ultrasound images. Objective: to investigate swallowing from the physiological perspective (ultrasound) and relate findings to the perceptive findings of vocal quality adjustments, seeking to describe larynx, pharynx, and muscular tension behaviors in different tasks. Method: swallowing and speech ultrasound samples were collected from 28 healthy adults, with ages ranging from 18 to 66 years of age, both male and female. To analyze ultrasound data related to swallowing, we used a modified proposal for measures related to duration and excursion of the hyoid bone (elevation, anteriorization and return). For the perceptive analysis, utterances regarding the speech corpus were analyzed by a juror trained in elements of vocal dynamics and in the Vocal Profile Analysis Scheme - VPAS-PB script of vocal quality. Swallowing and speech data were investigated statistically based on multivariate analysis. Results: the data found for duration and excursion of the hyoid bone and vocal quality measures can be positively related to findings. Likewise, vocal quality findings regarding adjustments in larynx height, speech (of vocal fold vibration modes) and muscular tension adjustments of the vocal tract showed positive correlations with swallowing ultrasound measures. Conclusion: ultrasound imaging enabled assessing swallowing of individuals with no particular complaints and relate findings to vocal quality adjustments. It is necessary to expand the existing database to have access to a system to clinically classify hyoid bone excursion measures, relating them to vocal quality adjustments of subjects with swallowing alterations